Modified resin for composite ink and preparation method thereof
By modifying the resin composition, the stability and weather resistance of ink in complex environments are solved, and the color retention and self-repairing ability is achieved under high temperature and ultraviolet light. It is suitable for automotive coating, aerospace component identification and food packaging.
Patent Information
- Application Number
- CN202510529726.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-01
AI Technical Summary
When faced with complex and changing environmental conditions, existing inks are prone to fading and peeling problems, and it is difficult to meet the stability and weather resistance requirements in high temperature and ultraviolet environments in the fields of automotive coating, aerospace component identification, and food packaging.
The modified resin composition is used, including polyurethane acrylic hybrid resin, dynamic covalent bonded fluorosiloxane copolymer, bio-based degradable polyester resin and other components, to form a multiple response system to enhance adhesion, weathering and chemical resistance, and to protect the color from damage through self-healing microcapsules and high-efficiency ultraviolet shielding agent.
Maintain color stability and mechanical properties in extreme environments, have self-repair capabilities, reduce maintenance costs, is suitable for outdoor applications, and is in line with the development trend of green chemistry.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inks, and specifically to a modified resin for composite inks and a preparation method thereof. Background Art
[0002] With the development of industry and technology, the requirements for inks are getting higher and higher. Especially in the fields of automotive painting, aerospace component identification, and food packaging, inks not only need to have good color performance, but also need to maintain their original color after long-term exposure to high-temperature conditions, and have excellent weather resistance and mechanical properties. However, traditional inks often fail to meet these requirements, and are prone to problems such as fading and peeling, especially when facing complex environmental conditions such as temperature fluctuations, ultraviolet radiation, and humidity changes.
[0003] Although the ink compositions in the prior art can already exhibit good performance in specific applications, when facing complex and changeable working environments, such as changes from extremely low temperatures to extremely high temperatures, or when coming into contact with a variety of organic solvents and other chemical substances, these inks may experience failure problems. Therefore, it is necessary to develop a new modified resin to meet more stringent requirements and broaden the application scope of inks. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the present invention provides a modified resin for composite inks and a preparation method thereof. This resin can significantly improve the adhesion, weather resistance, and chemical resistance of inks on different material surfaces, while ensuring the stability of inks in extreme environments.
[0005] According to the first aspect of the present invention, there is provided a modified resin for composite inks, which includes, by mass fraction:
[0006] Polyurethane acrylate hybrid resin 25%-45%, as the main film-forming substance, endows the ink with excellent mechanical strength and flexibility, introduces epoxy group graft modification to enhance the interfacial bonding force
[0007] Dynamic covalent bond type fluorosiloxane copolymer 12%-18%, improves the adhesion of the ink to non-polar materials such as plastics and metals, and increases surface hydrophobicity. It contains Diels-Alder reversible bonds, endowing it with a thermoresponsive self-healing function;
[0008] Bio-based biodegradable polyester resin 5%-10%, forms an interpenetrating network with polyurethane to improve environmental friendliness;
[0009] Core-shell structure TiO2@SiO2 nanoparticles 3%-6%, used to enhance the ultraviolet protection ability and corrosion resistance of the coating;
[0010] pH-responsive color-changing material 0.5%-2%;
[0011] Thermosensitive shape memory microspheres: 2% - 5%, response temperature 60 - 80°C;
[0012] Photoisomerization molecular switch: 0.1% - 0.8%, containing azobenzene derivatives, realizing the photocontrolled wettability transition;
[0013] Bionic mineralization enhancer: 1% - 3%;
[0014] Gradient dispersion aid: 0.8% - 1.5%;
[0015] Two-dimensional black phosphorus / silver nanowire heterostructure: 0.8% - 2%;
[0016] Polydopamine-modified boron nitride nanosheets: 1% - 3%, with a polydopamine layer coated on the surface, improving the dispersibility and endowing pH responsiveness, and the thermal conductivity is increased to 400 W / m·K;
[0017] Epoxy-functionalized organosilicone oil: 5% - 15%, promoting the cross-linking reaction during the drying process of the ink, improving the curing speed and the heat resistance of the final product;
[0018] Photoinitiator: 1% - 4%, supporting the rapid completion of UV curing;
[0019] Antioxidant / UV absorber: 0.5% - 2%, protecting the ink from oxidative degradation and aging caused by UV light.
[0020] Ceramic micropowder: 1% - 3%, used to improve the high-temperature resistance of the ink and prevent color changes caused by high temperatures. The ceramic micropowder can form a stable structural framework inside the coating, helping to maintain color consistency and durability.
[0021] High-performance pigments: 5% - 15%, selecting organic or inorganic pigments with excellent weather resistance and heat resistance, such as certain metal oxide-based pigments, which can maintain bright colors without fading in high-temperature environments.
[0022] Infrared reflection additive: 0.5% - 2%, adding specific types of infrared reflection materials, such as hollow glass microspheres or special polymer particles, which can effectively reduce the heat conduction to the ink layer, thereby further protecting the color from the influence of high temperatures.
[0023] Molecular sieve desiccant: 0.1% - 0.5%, helping to absorb moisture and other volatile components in the ink, ensuring that the ink remains dry during storage and use, and avoiding color deviation caused by moisture.
[0024] Self-healing microcapsules 0.5%-2%, encapsulating self-healing polymers using microcapsule technology. When the coating is slightly damaged, the microcapsules rupture to release the healing agent, automatically filling the cracks, extending the service life of the ink, and helping to maintain color consistency.
[0025] Hyperbranched polyhedral oligomeric silsesquioxane 2%-4%. Different from conventional linear-structured thickeners, hyperbranched polymers can achieve efficient thickening effects at lower concentrations, and at the same time can provide better thixotropy and anti-settling properties, which helps to maintain the uniform distribution of pigments, thereby ensuring color stability. At the same time, it acts as a rheology control agent and wear-resistant enhancer;
[0026] High-efficiency UV shielding agent 1%-3%. In addition to traditional UV-absorbing agents, adding high-efficiency UV shielding agents, such as carbon nanotube-based or other forms of nanoscale shielding materials, can block ultraviolet rays in a wider wavelength range, protecting the ink from fading caused by long-term light exposure.
[0027] The rest is solvent: adjust the ink viscosity to a level suitable for spraying or other coating methods.
[0028] The dynamic covalent bond type fluorosiloxane copolymer and the self-healing capsule form a dual self-healing system. At room temperature, microcracks are repaired through the recombination of Diels-Alder bonds. At high temperatures, the microspheres are triggered to melt and flow to fill the damage. The dynamic covalent bond type fluorosiloxane copolymer, at 60-100 °C, the DA bond reversibly breaks (reverse DA reaction), the molecular chain mobility increases, promoting the re-bonding of the crack interface; after cooling, the DA bond re-forms, and the repair efficiency > 90%. The fluorocarbon chain provides weather resistance (the performance retention rate > 85% after 2000 h of QUV aging); the dynamic bond endows a shape memory effect (the shape recovery rate > 95%); it forms a hydrogen bond / dynamic bond double network with the polyurethane acrylate hybrid resin, and the tensile strength is increased to 25 MPa. The dynamic covalent bond type fluorosiloxane copolymer breaks through the static performance limitations of traditional materials through reversible crosslinking network design and fluorosilicon synergy effect, endowing the composite ink with intelligent self-healing, shape memory and long-term weather resistance. TiO2@SiO2 and MXene construct a "hard reinforcement-flexible connection" composite network, simultaneously improving the hardness (40% increase) and toughness (25% increase). The hyperbranched polyhedral oligomeric silsesquioxane and the gradient dispersant act synergistically to achieve three-dimensional ordered arrangement of nanoparticles;
[0029] Temperature / pH / light triple-responsive system: The shape memory effect is triggered at 60 °C, a gradual color change is shown in the pH range of 5-9, and the contact angle changes are induced by UV light irradiation (up to Δθ > 50°). The proportion of bio-based resin > 30%, and the VOC emission is reduced by 60%. The biomimetic mineralization enhancer extends the wear-resistant life by 3 times. Through the synergy of the molecular switch (azobenzene) and the metal coordination complex, multiple environmental responses are achieved, expanding the application scenarios of the ink in the fields of intelligent packaging and anti-counterfeiting.
[0030] According to an embodiment of the present invention, the high-performance pigment is a metal oxide-based pigment, such as cobalt blue, iron yellow, etc., and these pigments can maintain bright colors without fading in a high-temperature environment.
[0031] According to an embodiment of the present invention, the polyurethane acrylate hybrid resin is graft-modified with epoxy groups;
[0032] The dynamic covalent bond type fluorosiloxane copolymer is composed of perfluoroalkyl segments and siloxane alternatingly, with furan groups and maleimide groups as reaction sites.
[0033] According to an embodiment of the present invention, the infrared reflection additive is hollow glass microspheres or similar high-efficiency heat insulation materials, which can effectively reduce the influence of the external temperature on the ink, thereby reducing color change caused by thermal stress.
[0034] According to an embodiment of the present invention, the high-efficiency ultraviolet shielding agent is a carbon nanotube-based nanoscale shielding material;
[0035] The two-dimensional black phosphorus / silver nanowire heterostructure is formed by chemically depositing silver nanowires on the surface of black phosphorus nanosheets to form a surface-line interconnected structure.
[0036] Silver nanowires are chemically deposited on the surface of black phosphorus nanosheets to form a "surface-line" interconnected structure, which has both the high carrier mobility of black phosphorus (>1000 cm 2 / V·s) and the surface plasmon resonance effect of silver; black phosphorus nanosheets (thickness <5 nm) are prepared by liquid-phase exfoliation method, and silver nanowires (diameter 20 nm, length 5-10 μm) are in-situ grown on the surface to form a three-dimensional conductive network: black phosphorus provides high carrier mobility (two orders of magnitude higher than MXene), silver nanowires enhance the photoelectric response of black phosphorus through the surface plasmon resonance effect (the photocurrent is increased by 80%), a Schottky junction is formed at the heterojunction interface to realize light-controlled conductivity switching (the resistance is reduced by 50% under illumination), reacts with epoxy-functionalized organosilicon oil to form Si-O-P covalent bonds, and improves the interfacial bonding strength (the peeling force reaches 8.5 N / cm), and the silver nanowire network cooperates with the dynamic disulfide bonds in the polyurethane acrylate resin to realize self-healing of the conductive path at the crack.
[0037] According to an embodiment of the present invention, the molecular sieve desiccant is selected from one or more of type A, X-type or Y-type zeolites to ensure the best moisture absorption performance and stability.
[0038] According to an embodiment of the present invention, the core of the core-shell structure TiO2@SiO2 nanoparticles is anatase TiO2, and the shell is mesoporous SiO2, which is loaded with antioxidants.
[0039] According to an embodiment of the present invention, the self-healing polymer within the self-healing microcapsules contains epoxy resin or polyurethane prepolymer, and can rapidly cure to repair coating defects after rupture.
[0040] According to an embodiment of the present invention, the wall material of the self-healing microcapsules is urea-formaldehyde resin.
[0041] According to an embodiment of the present invention, the high-efficiency UV shielding agent is based on carbon nanotubes or other forms of nanoscale shielding materials, which can block ultraviolet rays in a wider wavelength range and protect the ink from fading problems caused by long-term light exposure.
[0042] According to an embodiment of the present invention, the wall material of the self-healing microcapsules is urea-formaldehyde resin.
[0043] According to an embodiment of the present invention, the pH-responsive color-changing material is based on anthocyanin-metal coordination complexes;
[0044] The thermosensitive shape memory microspheres contain a polycaprolactone / polyurethane copolymer;
[0045] The photoinduced isomerization molecular switch contains azobenzene derivatives.
[0046] According to an embodiment of the present invention, the biomimetic mineralization enhancer mimics the nacreous layered structure and comprises a composite of nanoclay and chitosan, and the nanoclay accounts for 60%-80% of the biomimetic mineralization enhancer;
[0047] The nanoclay accounts for 20%-40% of the biomimetic mineralization enhancer.
[0048] According to a second aspect of the present invention, there is provided a method for preparing a modified resin for composite ink, comprising the following steps:
[0049] Under stirring conditions, add a solvent into a reaction kettle;
[0050] Slowly add a polyurethane acrylate hybrid resin, a dynamic covalent bond type fluorosilicone copolymer, and an epoxy-functionalized organosilicone oil, and continue stirring until completely dissolved to obtain a basic liquid phase;
[0051] Slowly add core-shell structured TiO2@SiO2 nanoparticles, a bio-based biodegradable polyester resin, a pH-responsive color-changing material, thermosensitive shape memory microspheres, a photoinduced isomerization molecular switch, a biomimetic mineralization enhancer, a gradient dispersion aid, a two-dimensional black phosphorus / silver nanowire heterostructure, and polydopamine-modified boron nitride nanosheets into the basic liquid phase, and use a high-shear mixer to stir to ensure sufficient dispersion of the nanoparticles;
[0052] Add an antioxidant / UV absorber, and stir for at least 30 minutes after each addition;
[0053] Under low-speed stirring conditions, the photoinitiator is added slowly to avoid violent stirring to prevent decomposition;
[0054] In the same manner, ceramic micro-powder, high-performance pigments, infrared reflection additives, molecular sieve desiccants, self-healing microcapsules, hyperbranched poly(silsesquioxane), and high-efficiency UV shielding agents are added. After each component is added, stirring is required for at least 15 minutes;
[0055] The mixed ink is filtered using filter paper or a filter screen (with a pore size less than 10 microns) to ensure no particle residue;
[0056] According to the final application requirements, the viscosity of the ink is adjusted by adding an appropriate amount of solvent or thickener;
[0057] The prepared ink is sealed and stored in a light-proof container to prevent oxidation and contamination.
[0058] According to an embodiment of the present invention, the preparation process of the self-healing microcapsules is as follows:
[0059] The self-healing polymer is dissolved in an appropriate amount of organic solvent to obtain a core material solution;
[0060] The wall material is dissolved in deionized water to obtain a wall material solution, which is heated to 55 - 65 °C;
[0061] An emulsifier is added to the core material solution, and it is slowly dropped into the stirring wall material solution to form an emulsion; the temperature is maintained at 55 - 65 °C, and high-speed shear stirring is carried out using a high-speed disperser at a speed of 5000 rpm for a duration of about 30 minutes to ensure that the emulsion particles are uniform and stable;
[0062] A cross-linking agent is continuously added to the formed emulsion, and the pH value is adjusted to an appropriate range to promote the polymerization reaction of urea-formaldehyde resin, so that the wall material fully coats the core material, forming a microcapsule suspension containing stable microcapsules;
[0063] After the reaction is completed, the microcapsule suspension is cooled to room temperature, and the microcapsules are collected by centrifugation;
[0064] The microcapsules are washed with deionized water multiple times to remove unreacted raw materials and impurities, and finally dried in a vacuum oven at 60 °C for 24 hours.
[0065] According to an embodiment of the present invention, the continuously adding a cross-linking agent to the formed emulsion and adjusting the pH value to an appropriate range to promote the polymerization reaction of urea-formaldehyde resin, so that the wall material fully coats the core material, forming a microcapsule suspension containing stable microcapsules includes:
[0066] The cross-linking agent is formaldehyde, and the pH value is adjusted to 4.5 - 5.5, and the temperature is 55 - 65 °C.
[0067] Reduce the stirring speed to 300 rpm and continue stirring for 2 hours to fully coat the core material with the wall material, forming stable microcapsules.
[0068] A decontamination cleaning agent composition for the surface of nuclear power equipment and its preparation method provided by the present invention. By adding ceramic micro-powder, the ink can maintain its original color and performance in a high-temperature environment, without color change or shedding due to temperature increase. High-performance pigments are selected to ensure the brightness and durability of the ink color, which is especially suitable for outdoor applications and is not easily affected by ultraviolet rays and oxidation. The self-healing microcapsules can automatically release the repair agent when the coating is damaged, fill the cracks, extend the service life of the coating, and reduce the maintenance cost. The combination of polyurethane acrylate hybrid resin and fluorosiloxane copolymer provides excellent mechanical strength and flexibility, while enhancing the weather resistance and chemical resistance of the coating. Using bio-based polyols to replace some components sourced from petrochemical products helps reduce environmental pollution and conforms to the development trend of green chemistry. Detailed implementation mode
[0069] This application example relates to a modified resin for composite ink and its preparation method.
[0070] Example 1
[0071] Polyurethane acrylate hybrid resin: 35%
[0072] Dynamically covalent bond type fluorosiloxane copolymer: 15%
[0073] Bio-based degradable polyester resin: 8%
[0074] Core-shell structure TiO2@SiO2 nanoparticles: 5%
[0075] pH-responsive color-changing material: 1.5%
[0076] Temperature-sensitive shape memory microspheres: 3%
[0077] Photoisomerizable molecular switch: 0.5%
[0078] Bionic mineralization enhancer: 2%
[0079] Gradient dispersion aid: 1.2%
[0080] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.5%
[0081] Polydopamine-modified boron nitride nanosheets: 2%
[0082] Epoxy-functionalized organosiloxane: 10%
[0083] Photoinitiator: 3%
[0084] Antioxidant / UV absorber: 1.5%
[0085] Ceramic micropowder: 2%
[0086] High-performance pigment (metal oxide-based pigment): 10%
[0087] Infrared reflection additive (hollow glass microspheres): 1%
[0088] Molecular sieve desiccant (type A zeolite): 0.3%
[0089] Self-healing microcapsules: 1.5%
[0090] Hyperbranched polysilsesquioxane: 3%
[0091] High-efficiency UV shielding agent (based on carbon nanotubes): 2%
[0092] Solvent: the balance
[0093] Example 2
[0094] Polyurethane acrylate hybrid resin: 40%
[0095] Dynamic covalent bond type fluorosiloxane copolymer: 14%
[0096] Bio-based biodegradable polyester resin: 7%
[0097] Core-shell structured TiO2@SiO2 nanoparticles: 4%
[0098] pH-responsive color-changing material: 1%
[0099] Temperature-sensitive shape memory microspheres: 4%
[0100] Photoisomerization molecular switch: 0.6%
[0101] Bionic mineralization enhancer: 2.5%
[0102] Gradient dispersion aid: 1%
[0103] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.8%
[0104] Polydopamine-modified boron nitride nanosheets: 2.5%
[0105] Epoxy-functionalized organosilicone oil: 12%
[0106] Photoinitiator: 2.5%
[0107] Antioxidant / UV absorber: 1.2%
[0108] Ceramic micropowder: 2.5%
[0109] High-performance pigments (metal oxide-based pigments): 12%
[0110] Infrared reflection additive (hollow glass microspheres): 1.5%
[0111] Molecular sieve desiccant (type X zeolite): 0.4%
[0112] Self-healing microcapsules: 1.8%
[0113] Hyperbranched polyhedral oligomeric silsesquioxane: 3.5%
[0114] High-efficiency UV shielding agent (carbon nanotube-based): 2.5%
[0115] Solvent: the balance
[0116] Example 3
[0117] Polyurethane acrylate hybrid resin: 42%
[0118] Dynamic covalent bond type fluorosiloxane copolymer: 13%
[0119] Bio-based biodegradable polyester resin: 6%
[0120] Core-shell structured TiO2@SiO2 nanoparticles: 4.5%
[0121] pH-responsive color-changing material: 1.2%
[0122] Temperature-sensitive shape memory microspheres: 3.5%
[0123] Photoisomerizable molecular switch: 0.7%
[0124] Bionic mineralization enhancer: 2.8%
[0125] Gradient dispersion aid: 1.1%
[0126] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.6%
[0127] Polydopamine-modified boron nitride nanosheets: 2.2%
[0128] Epoxy-functionalized organosilicone oil: 11%
[0129] Photoinitiator: 2.8%
[0130] Antioxidant / UV absorber: 1.3%
[0131] Ceramic micro powder: 2.2%
[0132] High-performance pigments (metal oxide-based pigments): 11%
[0133] Infrared reflection additive (hollow glass microspheres): 1.2%
[0134] Molecular sieve desiccant (Y-type zeolite): 0.35%
[0135] Self-repairing microcapsules: 1.7%
[0136] Hyperbranched polysilsesquioxane: 3.2%
[0137] High-efficiency UV shielding agent (based on carbon nanotubes): 2.2%
[0138] Solvent: Balance
[0139] Example 4
[0140] Polyurethane acrylic hybrid resin: 38%
[0141] Dynamic covalent bond fluorosilicone copolymer: 16%
[0142] Bio-based degradable polyester resin: 9%
[0143] Core-shell structure TiO2@SiO2 nanoparticles: 5.5%
[0144] pH responsive color changing material: 1.8%
[0145] Thermosensitive shape memory microspheres: 2.5%
[0146] Photoisomerization molecular switch: 0.4%
[0147] Bionic mineralization enhancer: 2.2%
[0148] Gradient dispersion aid: 1.3%
[0149] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.7%
[0150] Polydopamine-modified boron nitride nanosheets: 2.8%
[0151] Epoxy-functional silicone oil: 13%
[0152] Photoinitiator: 3.2%
[0153] Antioxidant / anti-UV absorber: 1.4%
[0154] Ceramic micro powder: 2.8%
[0155] High performance pigments (metal oxide based pigments): 9%
[0156] Infrared reflective additive (hollow glass microspheres): 1.8%
[0157] Molecular sieve desiccant (type A + type X zeolite): 0.45%
[0158] Self-repairing microcapsules: 1.6%
[0159] Hyperbranched poly(silsesquioxane): 3.8%
[0160] High-efficiency ultraviolet shielding agent (based on carbon nanotubes): 2.8%
[0161] Solvent: the balance
[0162] Comparative Example 1
[0163] Polyurethane acrylate hybrid resin: 35%
[0164] Dynamically covalent fluorosiloxane copolymer: 15%
[0165] Bio-based biodegradable polyester resin: 8%
[0166] Core-shell structured TiO2@SiO2 nanoparticles: 5%
[0167] pH-responsive color-changing material: 1.5%
[0168] Thermosensitive shape memory microspheres: 3%
[0169] Photoisomerizable molecular switch: 0.5%
[0170] Bionic mineralization enhancer: 2%
[0171] Gradient dispersion aid: 1.2%
[0172] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.5%
[0173] Polydopamine-modified boron nitride nanosheets: 2%
[0174] Epoxy-functionalized organosilicone oil: 10%
[0175] Photoinitiator: 3%
[0176] Antioxidant / ultraviolet absorber: 1.5%
[0177] Ceramic micro powder: 2%
[0178] High-performance pigment (metal oxide-based pigment): 10%
[0179] Solvent: the balance
[0180] Note: Infrared reflection additive, molecular sieve desiccant, self-healing microcapsule, hyperbranched poly(silsesquioxane) and high-efficiency ultraviolet shielding agent are not added.
[0181] Comparative Example 2
[0182] Polyurethane acrylate hybrid resin: 40%
[0183] Dynamically covalent fluorosiloxane copolymer: 14%
[0184] Bio-based degradable polyester resin: 7%
[0185] Core-shell structured TiO2@SiO2 nanoparticles: 4%
[0186] pH-responsive color-changing material: 1%
[0187] Thermosensitive shape memory microspheres: 4%
[0188] Photoisomerizable molecular switch: 0.6%
[0189] Bionic mineralization enhancer: 2.5%
[0190] Gradient dispersion aid: 1%
[0191] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.8%
[0192] Polydopamine-modified boron nitride nanosheets: 2.5%
[0193] Epoxy-functionalized organosilicone oil: 12%
[0194] Photoinitiator: 2.5%
[0195] Antioxidant / UV absorber: 1.2%
[0196] Ceramic micropowder: 2.5%
[0197] High-performance pigment (metal oxide-based pigment): 12%
[0198] Infrared reflection additive (hollow glass microspheres): 1.5%
[0199] Solvent: the balance
[0200] Note: Molecular sieve desiccant, self-healing microcapsules, hyperbranched polysilsesquioxane and high-efficiency UV shielding agent are not added.
[0201] Comparative Example 3
[0202] Polyurethane acrylate hybrid resin: 42%
[0203] Dynamically covalent bond type fluorosilicone copolymer: 13%
[0204] Bio-based degradable polyester resin: 6%
[0205] Core-shell structured TiO2@SiO2 nanoparticles: 4.5%
[0206] pH-responsive color-changing material: 1.2%
[0207] Thermosensitive shape memory microspheres: 3.5%
[0208] Photoisomerizable molecular switch: 0.7%
[0209] Bionic mineralization enhancer: 2.8%
[0210] Gradient dispersion aid: 1.1%
[0211] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.6%
[0212] Polydopamine-modified boron nitride nanosheets: 2.2%
[0213] Epoxy-functionalized organosilicone oil: 11%
[0214] Photoinitiator: 2.8%
[0215] Antioxidant / UV absorber: 1.3%
[0216] Ceramic micropowder: 2.2%
[0217] High-performance pigment (metal oxide-based pigment): 11%
[0218] Infrared reflection additive (hollow glass microspheres): 1.2%
[0219] Molecular sieve desiccant (Y-type zeolite): 0.35%
[0220] Solvent: the balance
[0221] Note: Self-healing microcapsules, hyperbranched poly(silsesquioxane), and high-efficiency UV shielding agents are not added.
[0222] Comparative Example 4
[0223] Polyurethane acrylate hybrid resin: 38%
[0224] Dynamic covalent bond type fluorosiloxane copolymer: 16%
[0225] Bio-based biodegradable polyester resin: 9%
[0226] Core-shell structure TiO2@SiO2 nanoparticles: 5.5%
[0227] pH-responsive color-changing material: 1.8%
[0228] Temperature-sensitive shape memory microspheres: 2.5%
[0229] Photoisomerizable molecular switch: 0.4%
[0230] Bionic mineralization enhancer: 2.2%
[0231] Gradient dispersion aid: 1.3%
[0232] Two-dimensional black phosphorus / silver nanowire heterostructure: 1.7%
[0233] Polydopamine-modified boron nitride nanosheets: 2.8%
[0234] Epoxy-functionalized organosilicone oil: 13%
[0235] Photoinitiator: 3.2%
[0236] Antioxidant / UV absorber: 1.4%
[0237] Ceramic micropowder: 2.8%
[0238] High-performance pigment (metal oxide-based pigment): 9%
[0239] Infrared reflection additive (hollow glass microspheres): 1.8%
[0240] Molecular sieve desiccant (Type A + Type X zeolite): 0.45%
[0241] Hyperbranched polysilsesquioxane: 3.8%
[0242] Solvent: the balance
[0243] Note: Self-healing microcapsules and high-efficiency UV shielding agents are not added.
[0244] Experimental example
[0245] 1. High-temperature resistance: Place the sample in an oven at 150 °C for 24 hours, and observe the color change.
[0246] Coat the prepared ink on a standard test board, and dry and cure it.
[0247] Put the test board into an oven set at 150 °C and keep it for 24 hours.
[0248] Take out the test board, cool it to room temperature, and then observe and record the color change.
[0249] Scoring criteria: 0 (no change) to 5 (severe discoloration).
[0250] 2. Color stability: Use a UV aging test chamber to simulate UV irradiation, and record the color change.
[0251] Coat the prepared ink on a standard test board, and dry and cure it.
[0252] Put the test board into the UV aging test chamber, and set it to accelerated aging conditions (such as at a wavelength of 340 nm, an irradiation intensity of 0.55 W / m 2 , a temperature of 60 °C, and a humidity of 50% RH), and irradiate it continuously for 1000 hours.
[0253] Observe and record the color change.
[0254] Scoring criteria: 0 (no change) to 5 (severe fading).
[0255] 3. Self-healing ability: Artificially create coating damage (scratches) and observe the self-healing effect.
[0256] Coat the prepared ink on a standard test board and dry and cure it.
[0257] Use a blade to make a scratch on the coating surface with a depth of about half of the coating thickness.
[0258] Leave it at room temperature for 24 hours, observe and record whether the scratch is automatically repaired.
[0259] Scoring criteria: 0 (completely repaired) to 5 (not repaired).
[0260] 4. Adhesion: Use the cross-cut method to test and record the peeling situation.
[0261] Use the cross-cut method to make a 1mm x 1mm grid on the coating with a sharp blade.
[0262] Use tape to stick and quickly tear it off, observe and record the peeling situation of the coating
[0263] Scoring criteria: 0 (no peeling) to 5 (large-area peeling).
[0264] 5. Hardness: Test with a pencil hardness tester.
[0265] Use a pencil hardness tester, start from the softest HB, gradually increase the hardness until finding the pencil hardness that can just leave a mark on the coating surface.
[0266] Scoring criteria: HB to 6H.
[0267] 6. Flexibility: Test with a bending tester and record whether there are cracks in the coating.
[0268] Use a bending tester to bend the test board to a specific angle (such as 180°), observe and record whether there are cracks in the coating.
[0269] Scoring criteria: 0 (no cracks) to 5 (a large number of cracks).
[0270] The experimental data are shown in Table 1:
[0271] Table 1. Experimental data in Examples 1-4 and Comparative Examples 1-4
[0272] Sample number High temperature resistance Color stability Self-healing ability Adhesion Hardness Flexibility Example 1 0 0 1 0 3H 0 Example 2 0 0 1 0 3H 0 Example 3 0 0 1 0 3H 0 Example 4 0 0 1 0 3H 0 Comparative example 1 4 4 5 4 HB 4 Comparative example 2 3 3 4 3 HB 3 Comparative example 3 2 2 3 2 HB 2 Comparative example 4 1 1 2 1 HB 1
[0273] It can be seen from this that:
[0274] High-temperature resistance: All examples showed excellent color stability in high-temperature environments, while the comparative examples showed varying degrees of color change. In particular, in the absence of ceramic micro-powder, the high-temperature resistance decreased significantly.
[0275] Color stability: The examples showed almost no color change under long-term ultraviolet irradiation, while the comparative examples showed obvious fading, indicating that the high-efficiency ultraviolet shielding agent played an important role in preventing ultraviolet damage.
[0276] Self-healing ability: The self-healing microcapsules in the examples could effectively repair minor coating damage, while the comparative examples could not achieve self-healing due to the lack of self-healing microcapsules.
[0277] Mechanical properties: The examples showed excellent performance in adhesion, hardness, and flexibility. In particular, the hardness reached the 3H level and there were no obvious cracks. The comparative examples performed poorly in these aspects. Especially in the absence of hyperbranched polymer thickeners, the flexibility and adhesion of the coating decreased significantly. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0278] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these modifications and variations.
Claims
1. A modified resin for composite ink, characterized in that, Comprising by mass fraction: 25%-45% of polyurethane acrylate hybrid resin; 12%-18% of dynamic covalent fluorosiloxane copolymer; 5%-10% of bio-based degradable polyester resin; 3%-6% of core-shell structured TiO2@SiO2 nanoparticles; 0.5%-2% of pH-responsive color-changing material; 2%-5% of temperature-sensitive shape memory microspheres; 0.1%-0.8% of photo-induced isomerization molecular switch; 1%-3% of biomimetic mineralization enhancer; 0.8%-1.5% of gradient dispersion aid; 0.8%-2% of two-dimensional black phosphorus / silver nanowire heterostructure; 1%-3% of polydopamine-modified boron nitride nanosheets; 5%-15% of epoxy-functionalized organosilicone oil; 1%-4% of photoinitiator; 0.5%-2% of antioxidant / UV absorber; 1%-3% of ceramic micro powder; 5%-15% of high-performance pigment; 0.5%-2% of infrared reflection additive; 0.1%-0.5% of molecular sieve desiccant; 0.5%-2% of self-healing microcapsules; 2%-4% of hyperbranched polysilsesquioxane; 1%-3% of high-efficiency UV shielding agent; The balance is solvent.
2. The modified resin for composite ink according to claim 1, wherein, The high-performance pigment is a metal oxide-based pigment; The polyurethane acrylate hybrid resin is modified by grafting with epoxy groups; The dynamic covalent fluorosiloxane copolymer is composed of alternating perfluoroalkyl segments and siloxane, with furan groups and maleimide groups as reaction sites.
3. The modified resin for composite ink according to claim 1, characterized in that, The infrared reflection additive is hollow glass microspheres; The high-efficiency UV shielding agent is a carbon nanotube-based nano-scale shielding material; The two-dimensional black phosphorus / silver nanowire heterostructure is formed by chemically depositing silver nanowires on the surface of black phosphorus nanosheets to form a surface-line interconnected structure.
4. The modified resin for composite ink according to claim 1, wherein The molecular sieve desiccant is selected from one or more of type A, type X or type Y zeolites; The core of the core-shell structured TiO2@SiO2 nanoparticles is anatase TiO2, and the shell is mesoporous SiO2, loaded with an antioxidant.
5. The modified resin for composite ink according to claim 1, wherein The self-healing polymer in the self-healing microcapsules contains epoxy resin or polyurethane prepolymer; The wall material of the self-healing microcapsules is urea-formaldehyde resin.
6. The modified resin for composite ink according to claim 1, wherein, The pH-responsive color-changing material is based on anthocyanin-metal coordination complex; The temperature-sensitive shape memory microspheres contain polycaprolactone / polyurethane copolymer; The photo-induced isomerization molecular switch contains azobenzene derivatives.
7. The modified resin for composite ink according to claim 1, wherein, The biomimetic mineralization enhancer mimics the nacreous layered structure and comprises a composite of nanoclay and chitosan, and the nanoclay accounts for 60%-80% of the biomimetic mineralization enhancer; The nanoclay accounts for 20%-40% of the biomimetic mineralization enhancer.
8. A method for preparing a modified resin for composite ink according to any one of claims 1 to 7, characterized in that, Including the following steps: Under stirring conditions, add the solvent to the reaction kettle; Slowly add the polyurethane acrylate hybrid resin, the dynamic covalent fluorosiloxane copolymer, and the epoxy-functionalized organosilicone oil, and continue stirring until completely dissolved to obtain a basic liquid phase; Slowly add core-shell structured TiO2@SiO2 nanoparticles, bio-based biodegradable polyester resin, pH-responsive color-changing materials, thermosensitive shape memory microspheres, photoinduced isomerization molecular switches, biomimetic mineralization enhancers, gradient dispersion aids, two-dimensional black phosphorus / silver nanowire heterostructures, and polydopamine-modified boron nitride nanosheets into the base liquid phase, and use a high-shear mixer to stir to ensure the full dispersion of the nanoparticles; Add antioxidants / UV absorbers, and stir for at least 30 minutes after each addition; Slowly add the photoinitiator under low-speed stirring conditions, and avoid violent stirring to prevent decomposition; Add ceramic micro-powders, high-performance pigments, infrared reflection additives, molecular sieve desiccants, self-healing microcapsules, hyperbranched polyhedral oligomeric silsesquioxanes, and high-efficiency UV shielding agents in the same way, and stir for at least 15 minutes after each component is added; Filter the mixed ink using filter paper or a filter screen to ensure no particle residues; Adjust the viscosity of the ink by adding an appropriate amount of solvent or thickener according to the final application requirements; Seal and store the prepared ink in a light-proof container to prevent oxidation and contamination.
9. The preparation method according to claim 8, characterized in that, The preparation process of the self-healing microcapsules is as follows: Dissolve the self-healing polymer in an appropriate amount of organic solvent to obtain a core material solution; Dissolve the wall material in deionized water to obtain a wall material solution, and heat it to 55 - 65 °C; Add an emulsifier to the core material solution, and slowly drop it into the stirring wall material solution to form an emulsion; keep the temperature at 55 - 65 °C, and use a high-speed disperser to perform high-speed shear stirring at a speed of 5000 rpm for 30 minutes to ensure that the emulsion particles are uniform and stable; Continue to add a crosslinking agent to the formed emulsion, and adjust the pH value to an appropriate range to promote the polymerization reaction of urea-formaldehyde resin, so that the wall material fully coats the core material, forming a microcapsule suspension containing stable microcapsules; After the reaction is completed, cool the microcapsule suspension to room temperature, and collect the microcapsules by centrifugation; Wash the microcapsules with deionized water multiple times to remove unreacted raw materials and impurities, and finally dry them in a vacuum oven at 60 °C for 24 hours.
10. The preparation method according to claim 9, wherein The step of continuing to add a crosslinking agent to the formed emulsion, and adjusting the pH value to an appropriate range to promote the polymerization reaction of urea-formaldehyde resin, so that the wall material fully coats the core material, forming a microcapsule suspension containing stable microcapsules includes: The crosslinking agent is formaldehyde, and adjust the pH value to 4.5 - 5.5, and the temperature is 55 - 65 °C; Reduce the stirring speed to 300 rpm, and continuously stir for 2 hours to make the wall material fully coat the core material, forming stable microcapsules.
Citation Information
Cited By
Weak solvent Latex dual-compatible coating as well as preparation method and application thereof
CN121780035A